Life at school an ethnographic study - Thapan, Meenakshi (Oxford University Press, 2006)
This book reconstructs the subjective interpretation of school life as perceived by teachers and pupils at Rishi Valley School (in Andhra Pradesh, India) which is often considered the hallmark of progressive education. It argues that the individual is significant to the schooling process in terms of the worlds that are created, managed, negotiated, contested, and developed. It also contends that the school's 'ideology', in the case of Rishi Valley, is especially explicit in underlining how the individual catalyses the transformation of the social world. The book explores the dilemmas and contradictions in the functioning of the transcendental and local orders in the everyday life of the school, and cites the fact that the students and teachers learn to negotiate their way through these contradictions and the conflict they may generate. It also considers the significant relations between philosopher Jiddu Krishnamurti's ideas and the institutions that seek to implement them. The Rishi Valley School is one such institution in India, with a dynamic character which is reflected in its ability to engage in a continuous process of transformation. The book also discusses ideology and education, school organization, school culture (rituals and ceremonies), teacher culture, formal and informal interaction between teachers, pupil culture, and freedom and constraint in teacher-pupil interaction.